2022
DOI: 10.1186/s12885-022-09603-3
|View full text |Cite
|
Sign up to set email alerts
|

miR-107 is involved in the regulation of NEDD9-mediated invasion and metastasis in breast cancer

Abstract: Background As a metastasis-related protein, NEDD9 has been reported in breast cancer (BC) metastasis research. However, there are few studies on the upstream regulators of NEDD9, especially involving the potential role of miRNAs. The purpose of this study was to explain whether miR-107 potentially regulates NEDD9, which may lead to invasion and metastasis of BC. Methods MCF-7 and MDA-MB-231 cells were transduced with lentiviruses to construct stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
3
6
0
Order By: Relevance
“…Notably, the levels in EV Q and EV UC were significantly higher than in the EV M condition, with EV M exhibiting the lowest recovery rate. We next assessed a specific set of six miRNAs known to be present in saliva [44] and for which dysregulations are associated to diverse pathologies [5358]. For all the targets, we clearly observed that miRNAs were enriched within EVs, confirming several previous observations [44, 45].…”
Section: Discussionsupporting
confidence: 77%
“…Notably, the levels in EV Q and EV UC were significantly higher than in the EV M condition, with EV M exhibiting the lowest recovery rate. We next assessed a specific set of six miRNAs known to be present in saliva [44] and for which dysregulations are associated to diverse pathologies [5358]. For all the targets, we clearly observed that miRNAs were enriched within EVs, confirming several previous observations [44, 45].…”
Section: Discussionsupporting
confidence: 77%
“…A total of 360 significantly different lncRNAs were identified in BC and adjacent normal tissues across the two databases (Figure 1E; Figure S1A; Table S5). The human BC cell lines MDA‐MB‐231 and MCF‐7 exhibited differences in aggressiveness and malignancy, with MDA‐MB‐231 being highly metastatic and malignant 29,32 . This finding was also corroborated by a wound healing assay (Figure 1F,G).…”
Section: Resultssupporting
confidence: 63%
“…Both miR-107 and PTEN are important players in carcinogenesis. miR-107 has a potential role in regulating NEDD9 in the invasion, migration and proliferation of breast cancer [ 49 ]. Additionally, miR-107 is hypothesized to deactivate the phosphatidylinositol 3-kinase (PI3K)/Akt pathway in a hypopharyngeal squamous cell carcinoma (HSCC) study [ 48 ].…”
Section: Discussionmentioning
confidence: 99%